Design and Implementation of Solar-Powered Pumping System in IKN Nusantara Area - Hebert Arthur Sigiro; Prabowo; Burhanuddin Halimi (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2024)
Solar-powered pumping systems are an alternative to providing a sustainable and independent water source. This system declines the dependency on fossil fuels, which generate no greenhouse gas emissions while operating. This paper presents the design, implementation, and performance testing of a solar-powered submersible water pump in Bumi Harapan and Bukit Raya Village to provide a supplementary water source for residents. To meet the daily water supply requirement of 10 m3 in two identical water towers, a 1.1 kW rated power water pump and a 2.2 kW photovoltaic system are chosen. A solar pump controller with the ability to switch power sources from photovoltaic to grid is used in the system to maintain a consistent water supply if needed. Based on performance simulations using PVSyst software, the designed systems cannot fulfill daily water requirements. However, they are expected to fill both water towers with a daily average supply of 5.78 m3 for the Bumi Harapan site and 9.23 m3 for the Bukit Raya site. These inabilities occurred because the pumps must operate with an elevation head that is more remarkable than the specifications. Performance tests using a solar power meter (SPM) and power quality analyzer (PQA) showed that the electric submersible pump (ESP) will supply water with a flow rate that depends on solar irradiance. Based on the data collection, the ESP successfully operates near its rated capacity during the peak sun hour.